ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI KINERJA SISTEM INFORMASI AKUNTANSI PADA DINAS TANAMAN PANGAN DAN HORTIKULTURA PROVINSI SUMATERA UTARA - Muhammad Arifin Pasaribu; Alistraja Dison Silalahi; Ardhansyah Putra Hrp (Program Studi Akuntansi Fakultas Ekonomi UMN AL Washliyah, 2022)
Accounting information system performance is the result of work from a series of accounting data that can be achieved by a person or group of people in an organization in accordance with their respective authorities and responsibilities, legally, not violating the law, and in accordance with moral ethics which in the end becomes a accounting information that includes transaction processing and information technology. The benefits of research relate to researchers, managers, agencies or institutions where research is carried out, professional organizations, scientific development and broad implementation of development. With the achievement of research objectives, this goal can be used by anyone as a user of research results and for needs. From the research results, it is known that User Participation and System Development Formulation are Factors Affecting the Performance of Accounting Information Systems at the Food Crops and Horticulture Department of North Sumatra Province. Meanwhile, Personnel Capability and Education and Training Programs are not Factors Affecting the Performance of Accounting Information Systems at the Department of Food Crops and Horticulture, North Sumatra Province.